South Africa : Selected Economic Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1996)
This Selected Economic Issues paper examines economic development in South Africa during 1995-96. The paper highlights that in 1995, the economy of South Africa grew by 3.3 percent, the third consecutive year of economic growth, and it is expected to grow between 3 1\2 and 4 percent in 1996. Some aspects of the unemployment problem are addressed in this paper. The paper also focuses on the implications for policy of the steps taken in 1994 and 1995 to establish an outward-oriented economy, after many years of effective autarky.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet